Relationship Between Maladaptive Cognition and Internet Addiction in Chinese Adolescents: Moderated Mediation Analysis of Online Motivation and Effortful Control. - Zhang, Qin; Wang, Yun; Luo, Yuhan; Zeng, Weixi; Cui, Qian (International Journal of Mental Health & Addiction, 2020)
This study explored the effect of online motivation and maladaptive cognition on adolescent Internet addiction and examined whether this process was moderated by effortful control. Cluster sampling was used to recruit 1221 middle school students as subjects (mean age = 13.45 years; 49.5% girls). The subjects completed an Internet addiction questionnaire, a maladaptive cognition questionnaire, an online motivation questionnaire, and an effortful control questionnaire anonymously. Results indicated that (1) maladaptive cognition exerted an indirect effect on Internet addiction via the complete mediating effect of online motivation, with sex, grade, and socioeconomic status controlled for; (2) this indirect effect was moderated mildly by effortful control and was stronger in students with lower levels of effortful control relative to that observed in students with higher levels of effortful control. Therefore, the results showed both mediating and moderating effects on the relationship between adaptive cognition and Internet addiction.